Ethnoveterinary survey of plants used for the control of gastrointestinal nematodes in sheep at three agro-ecological zones in the Eastern Cape Province of South Africa - Siza Mthi; Jean Rust; Sive Tokozwayo; Nkululeko Nyangiwe; Thobela L. Tyasi; Zimasa Dubeni; Mandla Yawa; Zuko Mpisane; Thenuis Morgenthal (AOSIS, 2021)
Background: With exception of the desert biome, all of South Africa's biomes occur in the Eastern Cape. The province is known to have high numbers of livestock that are mostly found in communal farming areas. Multi-drug resistance of gastrointestinal nematodes against major classes of conventional anthelmintics and the high cost of synthetic drugs calls for an urgent search for different control strategies of nematodes. Aim: A survey was conducted to identify and document plant species used to control gastrointestinal nematodes of livestock in Ciko, Goso and Upper Ngqumeya communities in the Eastern Cape Province. Setting: The study included filed observations and transect walks, as well as a standardized questionnaire given to 48 sheep farmers. Methodology: Forty-eight livestock farmers including men and women of mixed ages were interviewed. The information was obtained through the use of a structured questionnaire, field observations and transect walks. Data generated were analysed using descriptive statistics with frequency of citation (FC) and relative frequency of citation (RFC) as quantitative. Results: A total of 11 plant species from different genera were reportedly available and used to control gastrointestinal nematodes. Aloe ferox (0.67) and Zanthoxylum capense (0.44) had the highest values of RFC followed by Strychnos henningsii (0.23) and Elaphantorhhiza elephantine (0.21) and were widely known by the people of the study areas. The three most frequently used plant parts were leaves, roots and bark accounting for about 36.4%, 27.3% and 27.3%, respectively. The ethnoveterinary medicines were prepared in the form of decoctions and infusions. Oral administration of the concoctions was the only route of administration. The major constraints of sheep production as perceived by the farmers were prevalence of internal (36%) and external parasites (18.1%). All medicinal plants used were native and collected from the wild. The most dominant life forms were trees (45.4%), followed by herbs (36.4%) and shrubs (18.2%). Homestead expansion was ranked as the major threat (26%) to medicinal plants followed by firewood (21%). In-situ (protection through rangers) was the most frequently mentioned (67%) conservation practice used by farmers to protect the loss of medicinal plants followed by ex-situ (33%). Conclusion: In the light of data gathered on the surveyed plants, it appeared the plants play a role in the healthcare of sheep in rural communities. Further studies are required to analyse the plants for their chemical composition and biological properties.